Metabolic Profile of Strawberry Fruit Ripened on the Plant Following Treatment With an Ethylene Elicitor or Inhibitor - Reis, Leticia; Forney, Charles F.; Jordan, Michael; Munro Pennell, Kathleen; Fillmore, Sherry; Schemberger, Michelle O.; Ayub, Ricardo A. (Frontiers in Plant Science, 2020)
Strawberry is the most studied non-climacteric fruit for understanding the role ethylene in the ripening regulation. However, previous studies on the effects of ethylene on strawberry ripening were conducted with detached fruit. Thus, the aim of this work was to determine the effect of ethylene and the ethylene-action inhibitor 1-methylcyclopropene applied at different developmental stages on important physical-chemical attributes of ripe ‘Albion’ strawberry. Fruit at four developmental stages that remained attached to the plant were dipped in one of three treatment solutions (Ethephon, inhibitor 1-methylcyclopropene, and water), plus one absolute control that received no dip. Following treatment, when immature fruit were fully red or 24 h after treatment for red-treated fruit, strawberry fruit were assessed for physicochemical properties (weight, length, diameter, firmness, color, titratable acidity, soluble solids, pH, total phenolics, sugar, organic acid, amino acid, and volatile composition). The days following treatment required for fruit to ripen were also recorded. Treatments did not affect the rate of ripening nor fruit color, titratable acidity, pH, soluble solids, total phenolics, sugars or organic acids of ripe fruit. Ethephon affected fruit weight, diameter, length, firmness, anthocyanins, amino acids and volatiles, but these effects were dependent on fruit developmental stage at which the treatment was applied. When green fruit were treated with ethephon, ripe fruit had larger diameter and mass. Ethephon treatment of white fruit resulted in ripe fruit having greater anthocyanin content. Treatment of pink fruit resulted in ripe fruit having smaller diameter, length, and mass and greater firmness. Treatment of red fruit with ethephon altered fruit volatile composition, increasing concentrations of ethyl- and acetate-esters, which were reduced by the 1-MCP treatment. Ethephon treatment increased concentrations of 11 of the 19 free amino acids measured in ripe fruit with treatment of green and white fruit having the greatest effect. A total of 41 volatile compounds had significant correlations with 14 amino acids. While ethylene did not stimulate typical ripening of strawberry fruit, it does appear to alter fruit development and metabolism. The physiological effects of ethylene on strawberry fruit appears to depend on the developmental stage of the fruit.